Ammonium hexafluorosilicates: a new type of anti-caries agents - V. O. Gelmboldt; V. Yu. Anisimov (The State Expert Center of the Ministry of Health of Ukraine, 2019)
It is known that dental caries is one of the most common diseases; for children, this pathology ranks first among chronic diseases and has the character of a pandemic. In the modern arsenal of means for the treatment and prevention of caries, fluoride preparations - sodium, potassium fluoride, tin difluoride, sodium monofluoridephosphate, diammine silver fluoride - occupy the leading positions. In recent decades, ammonium hexafluorosilicate and hexafluorosilicates of organic ammonium cations, which have certain advantages over traditional fluoride preparations, have been actively studied as promising anti-caries and hypo-sensitive agents. The aim of this review is to systematize and analyze literature data, reflecting existing experience in the field of synthesis methods, studying the structure, physicochemical properties and biological activity of ammonium hexafluorosilicates as potential anti-caries agents. The general method for the synthesis of ammonium hexafluorosilicates is the interaction of the corresponding base, or its salt, in methanol, ethanol or another solvent with stoichiometric or excess amount of hydrofluoric acid. The structure of ammonium hexafluorosilicates, which are typical supramolecular compounds, is described. Using the example of pyridinium hexafluorosilicates, the relationship between water solubility and structural characteristics of salts was demonstrated. Identification methods have been proposed for the combination of cetylpyridinium hexafluorosilicate. The results of determination of acute toxicity for a number of hexafluorosilicates in animal experiments are given. Studies of the antibacterial activity of hexafluorosilicates are described. It is shown that hexafluorosilicates significantly reduce the number of carious lesions and their depth, and significantly exceed sodium fluoride in all indicators. The feasibility of their use for the prevention of periodontitis is demonstrated. A technological scheme for obtaining a gel containing cetylpyridinium hexafluoro silicate has been proposed. General methods for the synthesis of ammonium hexafluorosilicates include the interaction of an organic base or the corresponding hydrochloride in a solvent medium with an excess of hydrofluoric acid silica. In the crystal structures of hexafluorosilicates, hydrogen bond systems with the participation of fluorine ligands and H-donor fragments of cations perform the main structure-forming and stabilizing function. The solubility of hexafluorosilicates in water varies widely, which is determined by the nature of the ammonium cation and, in the case of pyridinium salts, is antibatically correlated with the number of strong and medium H-bonds in the salt structure. The degree of hydrolysis of hexafluoro silicates in 1×10-4 М aqueous solutions is high and in some cases reaches practically quantitative values. The results of the determination of the acute toxicity of ammonium hexafluorosilicates make it possible to classify these compounds as moderately toxic substances. All studied ammonium hexafluorosilicates exhibit high caries preventive activity, significantly reducing the number and depth of carious lesions, while simultaneously significantly improving the biochemical parameters of dental pulp and periodontal bone tissue. Ammonium hexafluorosilicates can be used as new effective anti-caries and hypo-sensitive agents.